Biossorção de Mn(II) por vagem de Moringa oleífera a partir de águas contaminadas - Pinto, Laura Adriane de Moraes (2016)
The increasing pollution of surface waters, caused groundwater to be further explored becoming a new source of supply worldwide. Manganese is naturally present in groundwater and even at low concentrations can cause a number of problems in water quality, making its removal essential. The presence of manganese in water is a concern for both population and industry, quality water is a prerequisite of great importance for any safe food production. The incidence of manganese in water is directly linked to oxidation and corrosion of pipes, as well as being primarily responsible for adding odor, metallic taste and blackened coloring to water in distribution and supply systems. Manganese (Mn) is an essential microelement, involved in bones and cartilage mineralization, particularly in children in the growth phase. However, high concentrations are toxic to humans and animals, may cause neurotoxic effects, thus, its removal before consumption is essential. In this context, this work objective was to find alternative methods for removing manganese of consumption and food production water. Initially, the moringa pods were collected in the city of Aracajú- SE. They were then washed for removing dirt, and dried in an oven at 60ºC for 24 hours. After drying, the material was subjected to particle size patterning of 0,32 mm and this material then received the name of non-treated pods (VAI). The agent treatment NaOH 0,1mmol (Synth, 97% purity) was evaluated as a basic agent and HCl 0,1 mmol L-1 (Nuclear 36,5% purity) as an acid agent for its ability to improve the Mn sorption by biomass. The pretreatment was carried out following the methodology described by Kumar and Gaur (2011), where 50 mg of untreated biosorbent was added to 50 mL of treating agent and stirred at 80 rpm for 30 min at 25°C. Subsequently the biomass was centrifuged (300 rpm, 15 min), the supernatant discarded and the pellet washed with Milli-Q water until neutral pH, then treated biomass was dried in an oven at 60 °C to constant weight. After drying the material was subjected to particle size standardization process, to obtain particles with a size of 0,32 mm. The pretreated acid pod was named VTA pod, the basic pre-treated pod was named VTB, all were evaluated for their manganese removal ability from tested water. The biosorbents were characterized by EDS, SEM and FTIR. The experimental data was kinetically analyzed and it was found that the biosorption by nine different adsorbents followed pseudo-second order kinetics, with a residence time of 30 min for all the pods. The equilibrium data was analyzed using the Langmuir and Freundlich isotherm model, and the more appropriate model for all adsorbents was Freundlich, confirming the heterogeneous nature of the biosorbents. The thermodynamic properties were also evaluated and confirmed the spontaneous nature of reaction, as the biosorption process by pods viability. This study revealed that the basic treatment promoted an improvement in Mn (II) removal capacity for all the adsorbents. The best removal results were obtained using a pH 6,0, 0,50 g of adsorbent in a contact time of 60 minutes. The most efficient biosorbent for the manganese removal was the basic treated pod, obtaining 94% removal, followed by the integral pod (VAI) with 82% and last, the acid pod (VTA) with 61% of removal. The usage of Moringa oleífera as adsorbent is an attractive option for the treatment of Mn polluted water, since beyond being a natural product of easy obtainment it is a renewable and biodegradable material. The biosorption can be adopted as a pre-treatment for groundwater with industrial purpose, helping not only with health maintenance but also with the improvement of equipment lifespan.